THE CHALLENGE OF ONLINE LANGUAGE LEARNING AND TEACHING: INCLUSIVE CONTENT AND MOTIVATION ENHANCEMENT - MA Liisa Wallenius; Ieva Brazauskaite-Zubaviciene (Mokslo Taikomieji Tyrimai Lietuvos Kolegijose, 2021)
The pandemics of COVID-19 has reinforced online learning and teaching. Online learning and teaching are becoming even more common than contact learning and teaching. For many language teachers, it is becoming a challenge for the methodology they used to apply. The methods had to be converted from a teacher-centred approach to a studentcentred approach. Even more of the study content had to be reoriented to student autonomy in learning. The aim of the paper is to share good practice of four international projects and four online language teaching aids to contribute to an inclusive content and motivation enhancement of online language learning. The first example is the first portal is Smart svenska (Smart Swedish) developed as part of an Aalto Online Learning project (A!Ole) financed by Aalto University. The second portal is a multi-disciplinary and open-access digital language learning portal called Svenskstudier fÃ¶r hÃ¶gskolestuderande (Swedish for higher education), financed by the Finnish Ministry of Education. The third international project and platform of online activities is Erasmus KA2, "Interactive Digital Content Platform to Share, Reuse, and Innovative in the Classroom" (INDIE), financed by the EU. The fourth international project is Nordplus Nordinc Languages, "Multilingualism as a Key to Enhance Students' Employability", financed by the Nordic Council of Ministers. All the analysed learning environments have a common aim which is to encourage student autonomy when learning. The aim is to motivate students by giving them more responsibility and autonomy for their own learning, i.e. student empowerment.